Approaching Artificial Intelligence in Designing Visual Aids for Teaching Mathematics at High Schools - DUY, Thi Thai Nhat; PHU, Du Xuan; DUY, Nguyen Hoang (PEARSON JOURNAL, 2025)
Today, artificial intelligence has been widely applied in many areas of society, especially in Education. AI tools, increasingly designed to be smarter, have been helpful for many teachers in their instructional tasks. This report presents some research findings on the application of AI tools in designing visual aids for teaching Mathematics at the high school level. Some ideas from the report may suggest trends in applying AI tools to the teaching process in education.